Der aktuelle Forschungsstand zum Großen Damm von Marib, Jemen, nach der Winterkampagne 2005/2006 - Vogt, Burkhard (Zeitschrift für Archäologie Außereuropäischer Kulturen, 2023)
The 2005/2006 investigations at the Northern Sluice of the Great Dam at Marib, Yemen, in its present state constructed by king Abraha in 548 AD, produced many fi ndings that shed a different light on its architectural evolution, its functioning and also on its ultimate failure. New data from the gravity walls, spillway, stilling basin, and the reservoir as well as an updated understanding of the repair works may affect the reconstruction of the sedimentological history and also of the human occupation in the oasis of Marib. The main result of the fi eldwork is the discovery of an earlier sluice construction probably to be attributed to the Himyarite king Sharahbil Yafur in 456 and that of a preceding primary channel built by an anonymous earlier king. Der Artikel wird zeitnah als PDF verfügbar sein.